Localization and characterization of gastrin/cholecystokinin-like immunoreactivity in the central nervous system of Aplysia californica - Vigna, SR (J Neurosci, 1984)
Gastrin/cholecystokinin-like immunoreactivity (G/CCK-LI) was localized by immunocytochemistry in neurons in the central nervous system of Aplysia californica. Neuronal cell bodies were specifically immunostained in the buccal, cerebral, pedal, and abdominal ganglia but not in the pleural ganglia. Neural G/CCK-LI processes were observed in the neuropil of all ganglia and connectives and in some but not all of the peripheral nerves examined. Somata containing G/CCK-LI ranged from 15 to 200 micron in diameter. Ganglionic G/CCK-LI was most efficiently extracted in neutral or basic solutions and consisted mainly of a substance eluting in a volume corresponding to a peptide of between 8 and 17 amino acid residues on gel filtration. This G/CCK-LI diluted in parallel to mammalian gastrin in radioimmunoassays using two antisera differing in their specificities for the bioactive COOH-terminal region of mammalian G/CCK. We conclude that G/CCK-LI is distributed widely in the central and peripheral nervous systems of Aplysia californica and that this immunoreactivity probably represents a small peptide which is similar but not identical to mammalian gastrins and cholecystokinins at the functionally critical COOH terminus.